Modeling Quantitative Value of Habitats for Marine and Estuarine Populations - Lipcius, Romuald N.; Eggleston, David B.; Fodrie, F. Joel; van der Meer, Jaap; Rose, Kenneth A.; Vasconcelos, Rita P.; van de Wolfshaar, Karen E. (Frontiers in Marine Science, 2019)
Coastal habitats (e.g., seagrass beds, shallow mud and sand flats) strongly influence survival, growth, and reproduction of exploited marine fish and invertebrate species. Many of these species have declined over the past decades, coincident with widespread degradation of coastal habitats, such that an urgent need exists to model the quantitative value of coastal habitats to their population dynamics. Demand for habitat considerations will increase as fisheries management contends with habitat issues in stock assessments and management in general moves towards a more ecosystem-based approach. The modeling of habitat function to support fishery species has, to date, been done on a case-by-case basis involving diverse approaches and types of population models, which has made it difficult to generalize about methods for incorporating habitat into population models. In this review, we offer guiding concepts for how habitat effects can be incorporated in population models commonly used to simulate the population dynamics of exploited fish and invertebrate species. We categorize population models based on whether they are static or dynamic representations of population status, and for dynamic, further into unstructured, age/size class structured, and individual-based. We then use examples to illustrate how habitat has been incorporated, implicitly (correlative) and explicitly (mechanistically), into each of these categories. We describe the methods used and provide details on their implementation and utility to facilitate adaptation of the approaches for other species and systems. We anticipate that our review can serve as a stimulus for more widespread use of population models to quantify the value of coastal habitats for exploited species, so that their importance can be accurately realized and to facilitate cross-species and cross-system comparisons. Quantitative evaluation of habitat effects in population dynamics will increasingly be needed for traditional stock assessments, ecosystem-based fisheries management, conservation of at-risk habitats, and recovery of overexploited stocks that rely on critical coastal habitats during their life cycle.